Sistem Informasi Kegiatan Kemahasiswaan Badan Eksekutif Mahasiswa: (Studi Kasus: BEM FTI Universitas Flores) - Anselmus Dhajo; Kristina Sara; Anastasia Mude (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2022)
The Faculty of Information Technology is one of the faculties at the University of Flores and oversees the Information Systems Study Program. The Faculty of Information Technology has several internal campus organizations, one of which is the Student Executive Board (BEM) FTI Uniflor. The recording and processing of management data as well as FTI BEM activity data and SME data are still done manually, which is recorded in the main book or typed in Microsoft Word and Excel so that it slows down the work system of the BEM management. Therefore, this problem can be solved by building a website-based application for an information system for student activities at the FTI Student Executive Board (BEM) using PHP as a programming language and MySQL database. The goal is to provide relief for BEM management in processing member data, activity data and making it easier to work on reports on activities carried out. With this information system, it is possible to improve the processing of management data, activity data, and SME data to be more effective and efficient. Observations, interviews, and literature searches are techniques for collecting data in research. While the development method uses the waterfall method and the blackbox testing method as a testing method. The results achieved from this research are, by building a web-based information system application where all data has been stored in a database, it is easy to process data for BEM management members, activity data, SME data and make activity reports.